2015
DOI: 10.5694/mja15.00272
|View full text |Cite
|
Sign up to set email alerts
|

Unprofessional behaviour on social media by medical students

Abstract: Social media use was nearly universal in the surveyed cohort. Posting of unprofessional content was highly prevalent despite understanding that this might be considered inappropriate, and despite awareness of professionalism guidelines. Medical educators should consider approaches to this problem that involve more than simply providing guidelines or policies, and students should be regularly prompted to evaluate and moderate their own online behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 10 publications
7
52
1
1
Order By: Relevance
“…However, our data showed no significant statistical gender difference similar to Avci et al’s study [11]. We found that YouTube is the most used website (93.8%) followed by Facebook (65.9%), which does not match with the results of Barlow et al’s study (Facebook, 99.4%; YouTube, 96.9%) [12]. On YouTube, it is easier to search for specific topics, to share it with others without the need for an account, and to find a variety of examples on the same subject.…”
Section: Discussioncontrasting
confidence: 83%
“…However, our data showed no significant statistical gender difference similar to Avci et al’s study [11]. We found that YouTube is the most used website (93.8%) followed by Facebook (65.9%), which does not match with the results of Barlow et al’s study (Facebook, 99.4%; YouTube, 96.9%) [12]. On YouTube, it is easier to search for specific topics, to share it with others without the need for an account, and to find a variety of examples on the same subject.…”
Section: Discussioncontrasting
confidence: 83%
“…There were no breaches of patient confidentiality found in our study. Similarly, Barlow et al reported a substantial level of unprofessional content (34%) amongst Australian medical students – mainly depictions of intoxication (301 students, 34.2%) or illegal drug use (14 students, 1.6%), or posting of patient information (14 students, 1.6%) . Kitsis et al noted significant differences in levels of self‐reported unprofessional (self‐posting of profanity, depiction of intoxication and sexually suggestive material) online conduct between students and faculty at an American university , suggesting that graduates have a greater awareness of their online responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has highlighted the increased incidence of such unprofessional behavior which has resulted in warnings to students and in some cases exclusion from their course (Chretien et al, 2009). This increase in adverse incident reporting has led to the development of policies to deal with this increase (Chretien et al, 2009;White et al, 2013), although this does not necessarily correlate to changes in behavior with some institutions still having to deal with unprofessional postings (Barlow et al, 2015). However, the issue is further complicated with students, doctors and patients all having different thresholds of what is acceptable to post online (Jain et al, 2014;Langenfeld et al, 2014;Langenfeld et al, 2015), and students appearing to be unaware of their professional vulnerability (Osman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%